Answer :

We have,

x + y = a + b …(i)


ax – by = a2 – b2…(ii)


To solve these equations, we need to make one of the variables (in both the equations) have same coefficient.


Lets multiply equation (i) by b, so that variable y in both the equations have same coefficient.


Recalling equations (i) & (ii),


x + y = a + b [×b


ax – by = a2 – b2



bx + ax = ab + a2


(b + a)x = a(b + a)


x = a


Substitute x = a in equations (i)/(ii), as per convenience of solving.


Thus, substituting in equation (i), we get


a + y = a + b


y = b


Hence, we have x = a and y = b.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics